THE LINKAGE DER AND NPM PROXY AGAINSTS TAX AVOIDANCE IN MANUFACTURING FIRM’S LISTED - Mia Muchia Desda; Mai Yuliza; Wahyu Indah Mursalini; Endarwita Endarwita; Yurasti Yurasti (Transpublika Publisher, 2024)
Taxes play a crucial role in a state's economy, serving as the primary source of revenue that enables government programs and infrastructure development. If tax revenues fall short of government targets, the intended objectives cannot be fully achieved. Indonesia, a country with significant natural resources and a strategic location, attracts both domestic and foreign businesses. However, tax compliance often conflicts with companies' goal to minimize tax expenses. This discrepancy leads to tax avoidance, where companies legally reduce their tax burden. This study aims to empirically examine the linkage of DER and NPM proxies with tax avoidance. Tax avoidance is measured using the cash effective tax rate (CETR) proxy. This causality study employs a quantitative research approach and involves twenty-one firms listed on the Indonesia Stock Exchange (IDX) during the 2016-2019 period, selected through judgment sampling. Panel data estimation is used in a regression model, with an estimation test conducted before hypothesis testing. The findings reveal that the DER and NPM proxies have a significant linkage with tax avoidance, both partially and simultaneously, contributing 87.38 percent. This study demonstrates that DER and NPM proxies can be used to identify tax avoidance practices in an empirical context, especially in Indonesia. Future research should consider case-study approaches to further enrich these findings.